Creating Jobs in Africa's Fragile States : Are Value Chains an Answer? - Dudwick, Nora; Srinivasan, Radhika (Washington, DC: World Bank, 2013)
What is the relationship between employment and conflict in fragile states? Although this question cannot be definitively answered, a large body of research suggests that in countries emerging from conflict, peace is likelier to endure if growth can be rapidly restored and translated into economic opportunities for large segments of the population. With a focus on Sub-Saharan Africa, this report attempts to address the challenge of employment and conflict in fragile states. First, it reviews employment- creation activities in fragile and conflict-affected environments to see which approaches appear most promising. Second, it presents specific recommendations for an employment-generation strategy over the medium term. The report argues that in Sub-Saharan Africa, where almost three-quarters of the labor force still works in agriculture, agricultural value chains may have the greatest potential to diversify rural economies, raise household incomes, and thereby contribute to stability. The core of value chain development involves strengthening relationships a critical task in fragile and post- conflict environments, where trust and social cohesion have been shattered. The argument made by this report is developed as follows: the remainder of this chapter briefly defines fragility and summarizes current thinking about its relationship to economic development. It then concludes with a brief discussion of the historical roots of fragility in Sub-Saharan Africa and the implications of this trajectory for the region's current and future development. The second chapter reviews prevailing approaches to employment in fragile and conflict-affected environments. The third chapter examines current and emerging practice directed at restoring private sector activity. It briefly reviews the World Bank's approach to private sector development in four post- conflict countries and then introduces new arguments for earlier and bolder efforts to restore economies and generate employment. Chapter four concludes with recommendations for building on this emerging practice.